The moderating role of vendor managed inventory on the bullwhip effect in the COVID-19 pandemic - Paul Mukucha; Felix Chari (Cogent Business & Management)
The study sought to determine the role of vendor-managed inventory and form postponement in mitigating against the bullwhip effect in the bakery industry. The bullwhip effect is referred to as demand distortions along the upstream supply chain that is caused by variances between supply and demand. The bullwhip effect was conceptualized by its indicators that are overstocking, obsolescence, and inventory holding costs. A survey of conveniently chosen 100 bakeries was conducted in the city of Harare, the capital city of Zimbabwe. The informants for individual bakeries were competent bookkeepers or qualified accountants. A factorial MANOVA and follow-up ANOVAs using the Bonferroni method were conducted. The study indicated statistically significant main effects and interaction effects for all the factors and concluded that all the indicators of the bullwhip effect can be mitigated if bakery businesses pursued either or both of the vendor-management inventory and the form postponement strategies. The managerial implications of this study were that bakery businesses can avoid the consequences of the bullwhip effect through investing in plant and equipment that enables form postponement, and strengthen the widely practiced vendor-management strategy.